From crisis to competitiveness : a proposal for a charter for hotels encouragement in the Caribbean - Caribbean Hotel Association (Caribbean Hotel Association [Santurce]PR, 1995)
Presents a proposal which seeks to optimise the hotel industry's potential to stimulate sustainable tourism growth and social and economic development, through capital investment, export promotion, job creation, small business expansion, education and training and stimulation of agro industry.